2017
DOI: 10.1128/jcm.01581-16
|View full text |Cite
|
Sign up to set email alerts
|

Detection of an Escherichia coli Sequence Type 167 Strain with Two Tandem Copies of bla NDM-1 in the Chromosome

Abstract: New Delhi metallo-␤-lactamase-1 (NDM-1)-producing Enterobacteriaceae has disseminated rapidly throughout the world and poses an urgent threat to public health. Previous studies confirmed that the bla NDM-1 gene is typically carried in plasmids but rarely in chromosome. We discovered a multidrug-resistant Escherichia coli strain Y5, originating from a urine sample and containing the bla NDM-1 gene, which did not transfer by either conjugation or electrotransformation. We confirmed the possibility of its chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…Though ST131 clones were predominantly reported worldwide, the STs observed in our study were striking for clustering in distinct phylogenetic lineages. ST167 was previously reported for its ability to carry bla NDM genes in China [38][39][40]. ST405 has been known as another global clonal group similar to ST131 [41] and has been reported to carry bla NDM genes in hospital settings [42], in addition to blaKPC-2 [43].…”
Section: Discussionmentioning
confidence: 98%
“…Though ST131 clones were predominantly reported worldwide, the STs observed in our study were striking for clustering in distinct phylogenetic lineages. ST167 was previously reported for its ability to carry bla NDM genes in China [38][39][40]. ST405 has been known as another global clonal group similar to ST131 [41] and has been reported to carry bla NDM genes in hospital settings [42], in addition to blaKPC-2 [43].…”
Section: Discussionmentioning
confidence: 98%
“…For example, a RB151 strain was reported to harbour 108 kb plasmid carrying NDM-1 gene on 4.8 Mbp chromosome [55]. E. coli Y5 isolate was found to have bla NDM-1 on chromosome as well [56]. The bla NDM-1 was also carried by more than one plasmid in some isolates.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a limited number of CRE have been found to carry carbapenemase genes on their chromosomes (3)(4)(5)(6). Notably, only two strains of Escherichia coli have been reported to carry chromosomally integrated bla NDM-1 in China and India (7,8). However, no such organisms have been found among Klebsiella pneumoniae strains.…”
mentioning
confidence: 99%
“…There have been several reports of Enterobacteriaceae carrying bla NDM-1 on their chromosomes, although only two cases have been reported for E. coli, in China (7) and India (8), but none have been reported for K. pneumoniae. A WGS analysis of Chinese E. coli strain Y5 showed that bla NDM-1 was embedded in its chromosome, and an ISCR1 element probably mediated the transposition of bla NDM-1 from a plasmid possibly derived from Proteus mirabilis PM58.…”
mentioning
confidence: 99%